Proton exchange membrane fuel cells - Qi, Zhigang (Boca Raton : CRC Press, 2014)
'The PEMFC is widely regarded as one of the most important technologies in the 21st century. Extensive research has been carried out by scientists and engineers in the past few decades, resulting in significant progress in materials, components, modules, control strategy, and system integration. This book enables the general reader to quickly understand and grasp the fundamentals of the PEMFCs. It gives experienced researchers the guidance they need to effectively tackle technical challenges. This book focuses on fundamentals, materials, components, system architecture, applications, and the current status. It provides complete coverage of this type of fuel cell with both general and experienced readers in mind'--
Includes bibliographical references (p. 329-331) and index.
Keywords: Proton exchange membrane fuel cells